Hemodynamic responses upon the initiation of thermoregulatory behavior in young healthy adults. Issue 2 (2nd April 2016) - Schlader, Zachary J.; Sarker, Suman; Mündel, Toby; Coleman, Gregory L.; Chapman, Christopher L.; Sackett, James R.; Johnson, Blair D.
ABSTRACT: We tested the hypotheses that thermoregulatory behavior is initiated before changes in blood pressure and that skin blood flow upon the initiation of behavior is reflex mediated. Ten healthy young subjects moved between 40°C and 17°C rooms when they felt 'too warm' (W→C) or 'too cool' (C→W). Blood pressure, cardiac output, skin and rectal temperatures were measured. Changes in skin blood flow between locations were not different at 2 forearm locations. One was clamped at 34°C ensuring responses were reflex controlled. The temperature of the other was not clamped ensuring responses were potentially local and/or reflex controlled. Relative to pre-test Baseline, skin temperature was not different at C→W (33.5 ± 0.7°C, P = 0.24), but was higher at W→C (36.1 ± 0.5°C, P < 0.01). Rectal temperature was different from Baseline at C→W (−0.2 ± 0.1°C, P < 0.01) and W→C (−0.2 ± 0.1°C, P < 0.01). Blood pressure was different from Baseline at C→W (+7 ± 4 mmHg, P < 0.01) and W→C (−5 ± 5 mmHg, P < 0.01). Cardiac output was not different from Baseline at C→W (−0.1 ± 0.4 L/min, P = 0.56), but higher at W→C (0.4 ± 0.4 L/min, P < 0.01). Skin blood flow between locations was not different from Baseline at C→W (clamped: −6 ± 15 PU, not clamped: −3 ± 6 PU, P = 0.46) or W→C (clamped: +21 ± 23 PU, not clamped: +29 ± 15 PU, P = 0.26). These data indicate that the initiation of thermoregulatory behavior is preceded by moderate changes in blood pressure and that skin blood flow upon the initiation of this behavior is under reflex control.